Pemetaan Kondisi Lamun di Perairan Sekitar Pulau Lepar Kabupaten Bangka Selatan - Suci Puspita Sari (Journal of Tropical Marine Science, 2019)
Status of seagrass ecosystem in South Bangka is needed to determine the indication of seagrass damage as a result of tin mining activities in coastal areas. Seagrass health conditions are analyzed through the density and seagrass cover so that the condition can be known. The method used to monitor seagrass conditions in this research is the utilization of remote sensing and geographic information systems (GIS) technology, using the algorithm of Depth Invariant Index (DII). Seagrass distribution based on the result of data processing of Landsat in 2017 shows that the Seagrass beds in the South Bangka water area of 4066.7 Ha. Species found from 7 sampling points, namely Enhalus acoroides, Thalassia hemprichii, Halophila ovalis, Cymodocea serrulata, Halodule Uninervis, and Cymodocea rotundata. Its seagrass conditions are generally included in the "poor" category.